Advancements in reperfusion rates and quality of care for ST-segment elevation myocardial infarction: a ten-year evaluation of Salvador's STEMI network - Roriz, Pollianna Souza; Ferreira, Isabella Bonifácio Brige; Pontes, Fabiana Benevides; Machado, Antônio; Aguiar, Tércio Caires; Matos, Marcos Antônio Almeida; Paiva Filho, Ivan Mattos; Menezes, Rodrigo Carvalho; Andrade, Bruno Bezerril (Frontiers in Cardiovascular Medicine, 2024)
Background Continuous investment and systematic evaluation of program accomplishments are required to achieve excellence in ST-segment elevation myocardial infarction (STEMI) care, especially in resource-limited settings. Therefore, this study evaluates the impact of problem-driven interventions on reperfusion use rate in a long-term operating STEMI network from a low- to middle-income country. Methods This is a healthcare improvement evaluation study of Salvador's public STEMI network in a quasi-experimental design, comparing data from 2009 to 2010 (pre-intervention) and 2019-2020 (post-intervention). There were evaluated all confirmed STEMI cases assisted in both periods. The interventions, implemented since 2017, included: expanding the support team, defining criteria to be a spoke, and initiating continuous education activities. The primary outcome was the rate of patients undergoing reperfusion, with secondary outcomes being time from door-to-ECG (D2E) and ECG-to-STEMI-team trigger (E2T). Results Over ten years, the network's coverage increased by 300,000 individuals, and expanded by 1,800 km2. A total of 885 records were analyzed, 287 in the pre-intervention group (182 men [63·4%]; mean [SD] age 62·1 [12·5] years) and 598 in the post-intervention group (356 men [59·5%]; mean [SD] age 61.9 [11·8] years). It was noticed a substantial increase in reperfusion delivery rate (90 [31%] vs. 431 [73%]; P = 001) and reductions in time from D2E (159 [83–340] vs. 29 [15–63], P = 001), and E2T (31 [21–44] vs. 16 [6–40], P = 001). Conclusion The strategies adopted by Salvador's STEMI network were associated with significant improvements in the rate of patients undergoing reperfusion and in D2E and E2T. However, the mortality rate remains high.